2012
DOI: 10.1021/bm301158j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Paclitaxel Release from a Biodegradable, Elastomeric, Poly(ester urethane)urea Bearing Phosphorylcholine Groups for Reduced Thrombogenicity

Abstract: Biodegradable polymers with high elasticity, low thrombogenicity, and drug loading capacity continue to be pursued for vascular engineering applications, including vascular grafts and stents. A biodegradable elastomeric polyurethane was designed as a candidate material for use as a drug-eluting stent coating, such that it was nonthrombogenic and could provide antiproliferative drug release to inhibit smooth muscle cell proliferation. A phosphorylcholine containing poly(ester urethane) urea (PEUU-PC) was synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 55 publications
3
66
1
Order By: Relevance
“…Its mechanical properties and degradation can be tuned by altering the chemical components [24,32,33]. Biofunctional and bioactive agents are capable of being incorporated with polyurethane urea through chemistry and engineering approaches [12,3436]. Its good biocompatibility has been verified from in vitro cell culture and in vivo implantation [24,3739].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its mechanical properties and degradation can be tuned by altering the chemical components [24,32,33]. Biofunctional and bioactive agents are capable of being incorporated with polyurethane urea through chemistry and engineering approaches [12,3436]. Its good biocompatibility has been verified from in vitro cell culture and in vivo implantation [24,3739].…”
Section: Discussionmentioning
confidence: 99%
“…Those include surface modification [911], polymer composition modification [8,12], nitric oxide release [1315] and drug release [1618]. Of these strategies, the drug release approach is an easy way to improve the biofunctions of biodegradable polymers.…”
Section: Introductionmentioning
confidence: 99%
“…29 The chemical tunability that has been employed for rational design of tissue engineering scaffolds can also be used to modulate the release of physicochemically diverse drugs from electrospun fibers. For example, Hong et al observed that grafting aminated phosphorylcholine onto the PLC-based poly(ester urethane) urea backbone slightly enhanced the release of paclitaxel from electrospun fibers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hong et al observed that grafting aminated phosphorylcholine onto the PLC-based poly(ester urethane) urea backbone slightly enhanced the release of paclitaxel from electrospun fibers. 29 Changing polymer chemistry may also increase the overall hydrophobicity of the bulk polymer and swelling ratio of the polymer matrix, with generally predictable effects on how the polymer interacts with hydrophilic or hydrophobic drugs encapsulated within the fibers. Similarly, Galperin et al observed more prolonged release of norfloxacin (NFL) from porous polyHEMA hydrogels with increasing fluorostyrene content in the bulk hydrogel.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, drug-releasing phosphorylcholine-grafted polyurethane vascular stents have been investigated in vitro for the inhibition of rat smooth muscle proliferation and demonstrated impaired platelet deposition with phosphorylcholine incorporation. [71] The hemocompatibility of MPC has been further utilized in attempting to recreate the luminal side of complex bioartificial organs exposed to blood. For instance, a polysulfone/MPC blend has been used to make asymmetrical membrane surfaces, with one side used to promote renal tubule epithelial cells and the other used to promote hemocompatibility to facilitate surface renal tube generation.…”
Section: In Vitro Studiesmentioning
confidence: 99%